Kontrol Edukasi Video Visual Smartphone Berbasis Selfcare terhadap Kecemasan dan Tekanan Darah Pasien Endoskopi dengan Pelayanan Anestesiologi - Slamet Mustofa; Sriyono Sriyono; Anna Surgean Veterini (Journal of Telenursing (JOTING), 2023)
This study aims to analyze the effect of self-care-based smartphone visual video education on the anxiety level and blood pressure of endoscopic patients with anesthesiology services. This research method uses a quasy experiment (pre-post test with control group design). The results showed that there were differences between the treatment and control groups. There were significant differences in anxiety (p=0.000), systolic blood pressure (p=0.011), and diastolic blood pressure (p=0.042). In the intervention group, there was a significant effect of smartphone visual video education on anxiety (p=0.000), systolic blood pressure (0.042), and diastolic blood pressure (p=0.008). In conclusion, self-care-based smartphone graphic video education affects the anxiety and blood pressure of endoscopic patients with anesthesiology services. Keywords: Education, Endoscopy, Anxiety, Blood Pressure, Video